Ensuring Human Rights at a New Stage of Uzbekistan’s Development - Ramatov, Jumaniyoz Sultanovich; Umarova, Rozigul (European Journal of Life Safety and Stability (2660-9630), 2021)
The article examines the issue of human rights in Uzbekistan, its indicators, religious and political views. Issues such as the formalization and implementation of individual remedy guarantees, international human rights treaties, and the protection and promotion of human rights were analyzed through relevant legislation and an independent judiciary.